Analysis of Shopping Budget at the Department of Women's Empowerment and Child Protection Community Empowerment Palembang City - Sari Muhiba; Harsi Romli; Lukita Tripermata (International Journal of Community Service & Engagement, 2022)
This study aims to analyze the preparation of a budget for the empowerment agency for women, child protection, and community empowerment in Palembang City. This research is a descriptive study using primary data and secondary data. The data collection technique is done by interview and documentation methods. The results showed that the women's empowerment office for child protection and community empowerment in Palembang City had applied the principles of Permendagri No. 13 of 2006 as a reference in the preparation of performance-based expenditures, but still faces obstacles in aligning the unit price in the RKA-SKPD, DPA, and budget reports. The increase in the amount of the budget from the DPPA to the Budget Report in 2017 was 9,01% and the decrease in 2018 was 1,34%.